A systematic literature review of empirical evidence on computer games and serious games - Connolly, Thomas M.; Boyle, Elizabeth A.; MacArthur, Ewan; Hainey, Thomas; Boyle, James M. (Computers and education, 2012)
This paper examines the literature on computer games and serious games in regard to the potential positive impacts of gaming on users aged 14 years or above, especially with respect to learning, skill enhancement and engagement. Search terms identified 129 papers reporting empirical evidence about the impacts and outcomes of computer games and serious games with respect to learning and engagement and a multidimensional approach to categorizing games was developed. The findings revealed that playing computer games is linked to a range of perceptual, cognitive, behavioural, affective and motivational impacts and outcomes. The most frequently occurring outcomes and impacts were knowledge acquisition/content understanding and affective and motivational outcomes. The range of indicators and measures used in the included papers are discussed, together with methodological limitations and recommendations for further work in this area. ► Largest review of computer games & serious games literature that we are aware of. ► 7392 papers were identified on positive impacts of games on users over 14 years. ► 129 papers reported empirical evidence about impacts on learning and engagement. ► A multidimensional approach has been developed to categorize games. ► This research provides a significant basis for future work in this area.